Design and fabrication of tandem rear part - Amirul Izwan, Abdullah (2013)
These theses give a detail explanation about the final year project fabrication of a tandem rear part. The purpose for this project is to fabricate a new tandem that is suitable for the child and the elder compare to the tandem nowadays that is being designed generally for the teenage and sport usage. There are many steps has been taken to design and fabricate this tandem. The modeling for this project has been made using Solidwork software. The fabrication process also undergoes many processes like cutting, welding, grinding, bending, sanding and also coating for the finalization of the project. Next, also being provided is a result of a simulation analysis for the product testing. Finally, the conclusion and the recommendation for the future plan of the project also being attached together with this thesis.